(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The administrative services of the Bureau of Jail Management and Penology (BJMP) primarily handle safeguarding, rehabilitation, and reformation programs in the persons deprived of liberty confined in the institution. The administration department shall provide services related to personnel, records, supplies, and cash management. Republic Act No. 6975, which is otherwise known as the “Department of the Interior and Local Government Act of 1990,” stated that the task of jail management and penology shall be the responsibility of the Bureau of Jail Management and Penology. As pursuant of this mandate, the BJMP, through consultative and participatory strategic planning sessions, should follow and value this mandate, as well as implement its vision, mission, powers, functions, objectives, and principles. In terms of the number of challenges brought about by certain circumstances, uniformity should be ensured in the discharge of functions by all BJMP personnel concerned to ensure that all special and standard services are delivered accordingly. The researcher utilized a descriptive method of research, which describes the characteristics of the population or phenomenon that is being studied. This methodology focuses more on the “what” of the research subject rather than the “why” of the research subject. The researchers also utilized questionnaires, unstructured interviews, and focused group discussions as research instruments to gather information. The respondents were described according to different demographic profiles. A total of 50% of the respondents are from the age range of 26–33 years old. A total of 90% of the respondents are male, 80% are married, and 70% are college graduates. The respondents assessed the capabilities of administrative personnel toward the delivery of services in Valenzuela City Jail in terms of information dissemination and timely updates and regarded these as “effective.” Meanwhile, the problems encountered that affect the capabilities of administrative personnel toward the delivery of services in Valenzuela City Jail were regarded as “less serious.” The results of the study can be used in crafting a guide to ensure that the capability of the bureau is more than enough in delivering the service needed and to address the problems in Caloocan City Jail properly.